ANALYSIS OF FASTING ON BLOOD TESTS - Imam Agus Faizal; Frisca Dewi Yunadi; Sodikin Sodikin; Ayuningtyas Ayuningtyas (Poltekkes Kemenkes Semarang, 2023)
As a procedure to obtain information with bodily fluid samples, a laboratory test is complementary to a diagnostic assessment. One parameter of laboratory tests is hematology, for which a blood profile is used to evaluate clinical conditions and provide diagnostic information about hematological abnormalities, prognosis, and response treatment. Nowadays, accessibility to laboratory tests has been made easier with medical checkups integrated into the Occupational Health and Safety program, which a company is obliged to have to check on its employees’ health status. Our study analyzed the results of fasting blood tests on the employees of The College of Health Sciences of Al-Irsyad Al-Islamiyyah Cilacap. This College is known for the practice of Islamic and religious values, including fasting, among its employees. Taking the employees as a population and samples, the research included variables of levels of erythrocytes, leukocytes, hemoglobin, and hematocrit in the descriptive analysis method. We gained eleven respondents, 8 males, and 3 females, and used a cluster sampling method with appropriate criteria. The data of obtained samples were analyzed and processed based on the interpretation of the results. The results of routine blood examinations on fasting showed 90.90% normal hemoglobin levels and 72.70% normal hematocrit levels. Conclusively, our results of the blood profile examination on hemoglobin and hematocrit in fasting people showed that fasting is metabolically healthy and produces no indication of anemia.